A novel haptic device design based on somatosensory superimposed stimuli. (1st February 2017) - Shima, K.; Sato, R.
Graphical Abstract: Abstract : The authors here outline a novel type of haptic equipment incorporating electrical and fingerpad stimulation as part of an applicable unit for virtual force generation. In the proposed approach, one of the user's fingerpads and its position are manipulated with a small mechanical device using an electrical stimulus. The outcomes of basic experiments involving healthy individuals and a small prototype unit that the user can wear indicated higher precision in virtual force perception with the proposed technique than exclusively with electrical stimulation. This underlines the applicability of the approach for the provision of force feedback with a virtual reality setup. In future work, the authors plan to examine a method to control the extent of fingertip stimulation in order to support the generation of sensations close to those provided by real objects.